Trends in tuberculosis incidence and mortality coefficients in Brazil, 2011-2019: analysis by inflection points - José Nildo de Barros Silva Júnior; Rodrigo de Macedo Couto; Layana Costa Alves; Daiane Alves da Silva; Isabela de Lucena Heráclio; Daniele Maria Pelissari; Kleydson Bonfim Andrade; Patrícia Bartholomay Oliveira (Pan American Health Organization, 2023)
Objective. To analyze the temporal trend of tuberculosis incidence and mortality rates in Brazil between 2011 and 2019. Methods. This was an ecological time series study of tuberculosis incidence and mortality rates in Brazil between 2011 and 2019. Data were extracted from the Notifiable Disease Information System and the Mortality Information System, and population estimates were from the Brazilian Institute of Geography and Statistics. Trends were analyzed by Joinpoint regression, which recognizes inflection points for temporal analysis. Results. The average incidence rate of tuberculosis in Brazil in the period was 35.8 cases per 100 000 population. From 2011 to 2015, this coefficient had an annual percentage change of -1.9% (95% CI [-3.4, -0.5]) followed by an increase of 2.4% (95% CI [0.9, 3.9]) until 2019. The average mortality rate between 2011 and 2019 was 2.2 deaths per 100 000 population, with an average annual percentage change of -0.4% (95% CI [-1.0, 0.2]). Amazonas was the only state with an increase in the annual average percentage variation for the incidence rate (3.2%; 95% CI [1.3, 5.1]) and mortality rate (2.7%; 95% CI [1.0, 4.4]) over the years, while Rio de Janeiro state had an increasing inflection for incidence from 2014 to 2019 (2.4%; 95% CI [1.4, 3.5]) and annual average of decreasing percentage variation (-3.5%; 95% CI [-5.0, -1.9]). Conclusions. During the period analyzed, a decreasing trend in incidence was observed between 2011 and 2015, and an increasing trend for the period from 2015 to 2019. On the other hand, no change in the trend for mortality was found in Brazil.